Development Of Digital-Era Human Resource Management Techniques: A Review-Based Study - Paul, Saima (International Journal of Psychosocial Rehabilitation, 2019)
This literature review work aims to analyze the development and significance of Digital HRM in international and Indian settings. Changes in technology have transfigured the HRM landscape as new technologies are integrated into the process to improve effectiveness, rationalization, and employee participation. It integrates the literature from well-known scholarly outlets, focusing on critical areas like recruitment and staff acquisition, employee induction, performance management, staff motivation, learning, development and training, and HR measurement and analytics. In line with this, this paper's review of the literature points to digital HRM as encompassing strategies informed by technologies to support the enhancement of organizational processes and outcomes based on the role of HR. The international experience confirms the usage of digital solutions in efficient workforce management, improving HR services, and integrating prognostic analytics for strategy development. On the other hand, among literature discusses more the prospects and constraints that Indian organizations encounter while implementing digital HRM practices, especially in small and medium enterprises (SMEs). Most of the findings regarding changes like HRM centre on the notion that digitalization has dramatically altered the roles and responsibilities of the profession and has required HR professionals to become strategic business partners equipped to manage digital change and workforce issues within the context of digital environments. The review also highlights the imperative competencies in HRM that point towards using technology appropriately, namely data analytics, integration of technology and positioning of technology. Concerning the study's strengths, the paper reveals the advantages of adopting digital HRM, including operational efficiency and employee satisfaction. However, there are certain limitations of the study about regional bias, limitations about method, and the ever-evolving nature of technology advancements. The research horizon for digital HRM in the future includes long-term outcomes, cross-country comparisons, and a qualitative examination of digital technologies' social and cultural impacts on HR activities, employees' health, and organizational management. Therefore, this paper advances a systematic review of current knowledge regarding digital-era HRM practices and directions for future research on enhancing the fit and efficacy of HR strategies for organizations operating in a world characterized by digitization.